Linking cell biology and ecology to understand coral symbiosis evolution. - Niels J Dingemanse; Annika Guse (PLoS Biology, 2024)
Understanding the evolution of coral endosymbiosis requires a predictive framework that integrates life-history theory and ecology with cell biology. The time has come to bridge disciplines and use a model systems approach to achieve this aim.